Pencegahan Stunting melalui Edukasi Gizi Ibu Hamil dan Balita di Nagari Balai Panjang - Tasya Julia Tara; Ali Imran Ahmad Husen; Dodi Mulyadi; Hambali Hambali (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Stunting remains a major public health issue in Indonesia, primarily caused by chronic malnutrition, inadequate maternal knowledge, and limited access to balanced nutrition. Community-based interventions, including student community service programs (KKN), have been widely recognized as effective approaches to increase public awareness and improve health behavior. This study aims to describe the implementation of a KKN program focused on stunting prevention through nutrition education for pregnant women and toddlers in Nagari Balai Panjang. The program involved health education sessions, counseling, and practical demonstrations of balanced nutrition tailored to local food resources. The results indicate an increase in participants’ knowledge and awareness regarding the importance of nutritional intake during pregnancy and early childhood. Previous studies highlight that maternal nutrition education significantly contributes to reducing stunting risk and improving child growth outcomes. In conclusion, the KKN program plays a strategic role in supporting government efforts to reduce stunting prevalence through community empowerment and education. Sustainable and collaborative approaches are needed to ensure long-term impact on maternal and child health.